Having fun with textiles - Medina, Sarah, 1960. (New York : PowerKids Press, 2008)
Presents step-by-step, illustrated instructions for eight art projects made with textiles, including a thank-you card, a woven mat, and a decorated T-shirt.
Includes index.
3.4
K-3
Keywords: Textile crafts -- Juvenile literature; Textile crafts; Handicraft; Textile crafts; Handicraft; Handicraft -- Textile crafts; Textile crafts